Reactivity of TNF-α, NF-κB, and TGF-β in Liver Tissue of Rats Due to the Sand Mussel Consumption - Öztürk, Ş; İrkin, LC (Journal of the Hellenic Veterinary Medical Society, 2023)
Toxic substances such as heavy metals have been reported to accumulate by aquatic organisms. In this study, it was aimed to investigate the histopathological changes that may occur in the liver parenchyma, the largest gland of the digestive system, by feeding the rats with sand mussel. The samples were analyzed for cadmium (Cd), lead (Pb), copper (Cu), and zinc (Zn) by ICP-OES). The liver tissue samples were stained with Hematoxylin-Eosin (H&E), and immuohitochemically staining inflamatory marker TNF-α, NF-κB, and fibrotic factor TGF-β. Heavy metal accumulation in sand mussel tissue suggests that it may triggers the toxicity in tissues with the consumption frequently that the hepatotoxic effect was quite severe especially in rats fed with sand mussel. Also immunoreactivity of TNF-α, TGF-β and NF-κB were observed in the liver cells of especially second group. As a result, aquatic ecosystem can be affected with environmental pollution. It has been shown that marine based food obtained from polluted areas can trigger the hepatotoxicity.